Biopolymers as a new paradigm in the plant disease management: Biopolymers as a new paradigm in the plant disease management - B M SANGEETHA,; K S V P CHANDRIKA,; R D PRASAD,; N B BHAT, (Journal of Oilseeds Research, 2023)
Changing climate makes great impact on the pest incidence which directly affects the global food production. There is a need for promising alternative for chemical pesticides. Biopolymer, chitosan is well known for its antimicrobial property and eco-friendly nature. We have synthesized speciality polymers using chitosan for seed treatment and foliar spray. Synthesized biopolymers showed antifungal activity against the phytopathogens (Aspergillus niger and Amphobotrys ricini) and 100per cent compatibility with the biocontrol agent Trichoderma harzianum Th4d. Results indicated the applicability of these particles as an alternative for the disease management.